2019
DOI: 10.1097/01.ogx.0000554821.40095.69
|View full text |Cite
|
Sign up to set email alerts
|

Physical Examination Techniques for the Assessment of Pelvic Floor Myofascial Pain: A Systematic Review

Abstract: (Abstracted from Am J Obstet Gynecol 2018;219:497.e1–497.e13) Myofascial pain is common in both women and men with chronic pelvic pain (CPP) and pelvic floor disorder symptoms. It is characterized by the presence of trigger points, tenderness to palpation, and local or referred pain and can result in debilitating CPP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
0
8
0
2
Order By: Relevance
“…Algological assessment is also important because possible myofascial pain is related to the severity of urinary incontinence and bowel symptoms such as the sensation of incomplete voiding 32,33 . Assessment of myofascial pain is outside the scope of nursing expertise in many countries; a practical discussion of assessment methods is given in a 2019 study cited in the bibliography of this article 34 .…”
Section: Resultsmentioning
confidence: 99%
“…Algological assessment is also important because possible myofascial pain is related to the severity of urinary incontinence and bowel symptoms such as the sensation of incomplete voiding 32,33 . Assessment of myofascial pain is outside the scope of nursing expertise in many countries; a practical discussion of assessment methods is given in a 2019 study cited in the bibliography of this article 34 .…”
Section: Resultsmentioning
confidence: 99%
“…Although there has always been criticism of the low intra‐ and inter‐rater reliability of physical exams, 55 there are recent investigations into a standardized set of objective measures of physical exam for pelvic floor 56 . Another possibility is to use physical measures of pelvic floor dysfunction to supplement the outcomes, including the strength (eg dynamometer), tone (eg myotonometry) and pain threshold (eg algometer).…”
Section: Discussionmentioning
confidence: 99%
“…This review suggests that standardized physical vaginal examination of pelvic floor muscles to detect tenderness be utilized to detect PFMP with the addition of an algometer or pressure device not required to improve diagnostic capability. Physical examination to detect tenderness appears most practical [15,16] with good reported inter- [18][19][20][21][22] and intra-rater [18,19,22] reliability. PFMP may occur either as an isolated diagnosis or in conjunction with other conditions including musculoskeletal [32,33], gastrointestinal [34][35][36], genitourinary [31,[37][38][39], gynaecological [6,40,41] and persistent pelvic pain [20,42] conditions.…”
Section: Principal Findingsmentioning
confidence: 99%
“…This review revealed a number of diagnostic tests for assessing PFMP including dynamometer [66], surface electromyography [66,76], algometry [53], morphometry [77,78], manometry [76] and questionnaires [7,8,22]. A recent systematic review of physical examination techniques to detect PFMP included 55 studies, however, only two assessed the examination itself, with most included studies being clinical reviews and prevalence studies [15]. In contrast, our review only reviewed studies designed to assess diagnostic capabilities to detect PFMP compared with physical examination.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation